Pengaruh Media Audio Visual Berbasis Video Animasi Terhadap Keterampilan Menceritakan Kembali Cerita Fiksi Peserta Didik - Rahmatiah Rahmatiah (BLAZE : Jurnal Bahasa dan Sastra dalam Pendidikan Linguistik dan Pengembangan, 2024)
This research aims to determine the influence of audio-visual media based on animated videos in learning the skills of retelling fictional stories for class IV students at SDN 306 Pasamai District. Belopa. The type of research used is pre-experimental design, including quantitative research. The location of this research was carried out at SDN 306 Pasamai, Belopa District, with a total of 31 students. There are two variables in this research, namely the independent variable which is the cause of the emergence or change in the dependent variable. Meanwhile, the dependent variable is influenced by the data because there are independent variables or variables. The instruments used in this research were learning outcomes tests and observation sheets. The data collection techniques used by researchers were interviews, observation, tests and documentation, as well as storytelling tests. The data analysis technique used is descriptive analysis technique. Based on these results, it can be concluded that audio-visual media based on animated videos has an influence on the skills of retelling fictional stories of class IV students at SDN 306 Pasamai.